The Effects of Total Quality Management Practices on Performance and the Reasons of and the Barriers to TQM Practices in Turkey. (15th March 2014) - Sadikoglu, Esin; Olcay, Hilal
Abstract : Previous studies reported mixed and ambiguous results of the relationship between TQM practices and performances. This study investigated impacts of TQM practices on various performance measures as well as the reasons and the barriers of the TQM practices of firms in Turkey. We used a cross-sectional survey methodology in this study, and the unit of the sample was at the plant level. The sample was selected from the member firms to Turkish Quality Association and the firms located in the Kocaeli-Gebze Organized Industrial Zone. We obtained 242 usable questionnaires, with a satisfactory response rate of 48.4 percent. We conducted exploratory factor analysis and multiple regression analysis. This study has shown that different TQM practices significantly affect different performance outcomes. Results revealed that primary obstacles that the firms in Turkey face were lack of employee involvement, awareness and commitment of the employees, inappropriate firm structure, and lack of the resources. It is recommended that firms should continue implement TQM with all variables to improve performance. Firms should improve employees' involvement/commitment/awareness to TQM, enhance firm structure, and provide resources to overcome the barriers that prevent effective implementation of TQM practices.